ANALISIS POTENSI SUMBER ENERGI ANGIN DI DESA SIMAN KABUPATEN LAMONGAN: ESTIMASI MENGGUNAKAN PEMODELAN SISTEM TURBIN ANGIN - Jauharotul Maknunah; Yussi Anggraini; Ahmad Husni Mubarok; Siti Duratun Nasiqiati Rosady; Eli Novita Sari (P3M Politeknik Negeri Indramayu, 2023)
Wind energy that can be utilized into electrical energy certainly requires sufficient wind speed so that the wind turbine can rotate and produce mechanical movement in the form of rotational torque which can then be converted into electrical energy. Before the application of the technology is carried out, this study is needed to examine the potential of wind energy produced in Siman Village, Lamongan Regency. To produce a power profile from wind energy sources, wind speed measurements are first carried out, followed by mechanical modeling and wind turbine electrical modeling. The maximum electric power generated from the simulation of electrical energy conversion using a wind turbine is 11.94 Watt with a maximum wind speed of 3.5 m/s. If converted in energy units, then in a day the wind energy that can be extracted into electrical energy is 286.56 Watt.h. When compared with the daily electrical energy needs in the household sector (9364 watt.h) the electrical energy generated through modeling is able to meet 3.1% of electricity needs in a day.